RESEARCH OF PROCESS OF FINANCIAL MONITORING ORGANIZING IN BANKS - Kovalenko, V.V. (The actual problems of regional economy development, 2017)
The article aims to study methods and tools for financial monitoring by banks. It is proved that one of the main global financial problems in recent years is increasing number of cases of banks participating in the money laundering. It causes banks huge losses, undermines the credibility of honest depositors, in addition, circulation of funds like these hurts the national economy. The article is to develop recommendations to improve the effectiveness of financial monitoring in banks. It is proved that the current model of the national financial monitoring system includes the following elements: the purpose of macroeconomic and microeconomic levels; principles; function; facilities; subjects; types of financial monitoring; methods of implementation and regulatory prevue regulation. It is proved that the major problems related to the financial monitoring of banks are the following: lack of legislatively established quality requirements of customer information; persons engaged in legalization of illegal incomes are highly qualified, which greatly facilitates them through the bank of suspicious transactions; the process of settlement bank failure in the conduct of questionable transactions.